The effect of cover crops on soil structure and the subsequent yield of sugar beet - Richards, Jake Peter (2020)
Pressure is mounting on policy makers and farmers to improve the sustainability of UK Agriculture. One area of improvement surrounds possible changes within crop rotations to improve soil health in tandem with increasing crop yield. The success of a cash crop, is widely determined by the structure of its growing media. In field crops this is considered as the structure of the soil which is responsible for allowing water and nutrient uptake as well as, particularly for root crops, providing a profile for unimpeded root growth. The effects of cover crops on the soil physical properties and the subsequent crop growth are considered in this thesis. By conducting glasshouse experiments using different cover crop species and soil volumes, the relationship between cover crop root growth, soil moisture and soil aggregation has been tested. This informed the development of a number of field experiments that have investigated the relationship between cover crops, soil structure and subsequent crop growth with typical UK climatic and soil conditions. It was hypothesised that cover crops improve the soil structure, prior to a cash crop, resulting in higher crop yield. Our findings have established that cover crops do influence the soil structure, demonstrated by aggregation in controlled environment experiments and soil porosity as seen in the field. However, this was greatly influenced by factors including soil texture, soil volume, cover crop growth and weather conditions. We fund that the growth of cover crops was most beneficial on soils with a low clay content where sugar beet yield was 10% greater following a cover crop than following stubble. This was as a result of lower water stress in response to greater soil porosity. Results showed that soil with a high clay content is susceptible to changes in soil aggregation. There is a link between soil conductivity and plant growth showing it is a useful proxy for water uptake. There is also a positive effect of cover crops on earthworm population. We found that overall cover crop root growth was directly related to above ground biomass and there was no benefit to combining cover crop species in favour of single species cover crop.